Analysis of nonlinear oscillator arising in the microelectromechanical system by using the parameter expansion and equivalent linearization methods - Hieu, D. V.; Thoa, N. T. K.; Duy, L. Q. (International Journal of Engineering and Technology, 2018)
In this paper, the nonlinear oscillator arising in the microbeam-based micro-electromechanical system (MEMS) is described. The motion equation of a microbeam is simplified into an ordinary differential equation by using the Galerkin method. The nonlinear ordinary differential equation is solved by using two methods including the Parameter-Expansion and Equivalent Linearization Methods. To verify the accuracy of the present methods, illustrative examples are provided and compared with other analytical, exact and numerical solutions.